Light utilization and excretion of organic matter by antarctic lake phytoplankton - Kaspar, Mark (Virginia Polytechnic Institute and State University, 1986)
Quantum yields () were determined for the phytoplankton of four perennially ice-covered lakes of southern Victoria Land, Antarctica. The phytoplankton communities of these oligotrophic lakes are dominated by cryptophytes, unicellular chrysophytes and flagellated chlorophytes. Quantum yields were calculated using a suggested value for the spectral extinction coefficient of chlorophyll a (k c )=0.016 and an empirical estimation of k c = 0.0328. Quantum yields ranged from 0.0045 to 0.156 using k c = 0.016, while were lower when calculated using k c =0.0328, ranging from 0.0022 to 0.076. Values of were comparable to values reported for phytoplankton elsewhere. Light utilization efficiencies () ranged from 0.006 to 1.46% and are among the lowest values yet reported from aquatic ecosystems. The estimations of indicate that the phytoplankton were efficient at trapping the low levels of photosynthetically active radiation present in these dimly lit lakes, while indicate that environmental conditions of these lakes are limiting their respective phytoplankton communities. Percent extracellular release (PER) of organic matter was greatest in the shallow depths studied in comparison to the mid-depths sampled. The shallower waters of these lakes were supersaturated with oxygen, brighter and probably nutrient limited. Photosynthesis in Chlamydomonas subcaudata Wille was 2.5 to 3.5 x less at supersaturated oxygen in comparison to saturated oxygen. The higher amount of PER in the shallow depths and the inhibition of photosynthesis in C. subcaudata by supersaturated oxygen indicates that the reduction of photosynthesis due to photorespiration might be limiting the development of the phytoplankton communities of these lakes. M.S.